1992
DOI: 10.1088/0953-8984/4/10/016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oxygen on charge transport in PDATS

Abstract: AbslracLWe examine the effect oxygen conlamination has on the recombination centre separation, trap density and defect ionization efficiency in PDATS single cryslals. We find that, wilh no Oxygen present, recombination centres are not delecled in sample lenglhs of up lo 9.8 mm. However. for chase samples contaminated with oxygen. we find interQenlre separations of only a few hundred microns. We also show that oxygen increases the trap density and t h e defeci ionization efficiency. Finally, we demonslrale that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Diacetylene polymers are quasi-one-dimensional photoconductors. The photoinduced electrical carrier mobility along the polymer chain direction has been measured to be about 5 cm 2 /V·s , and is 3−4 orders of magnitude higher than that perpendicular to the polymer chain direction. Diacetylene polymers have been utilized to study carrier motion along the chain in semiconductive conjugated polymer solids.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Diacetylene polymers are quasi-one-dimensional photoconductors. The photoinduced electrical carrier mobility along the polymer chain direction has been measured to be about 5 cm 2 /V·s , and is 3−4 orders of magnitude higher than that perpendicular to the polymer chain direction. Diacetylene polymers have been utilized to study carrier motion along the chain in semiconductive conjugated polymer solids.…”
Section: Introductionmentioning
confidence: 99%
“…This process is weak and thus the dissipation by the SWAP is also weak. However, Fisher found that carrier velocity is dependent on the electrical field at low field but tends to be saturated at 5000 m/s at electrical fields higher than 6.5 × 10 4 V/cm . He accordingly suggested that carrier motion along a chain may be that of the SWAP, but the observed motion is dominated by field-dependent trapping events at low fields.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations